Eucalypt diseases : current status in Brazil and scientometrics analysis of the major diseases and pathogens in the world - Santos, Ana Luiza Rati dos (2021)
The Brazilian forest-based sector is internationally recognized for its sustainable forest management and high productivity of its planted forests. In recent decades, innovative planting and cultivation technologies have allowed for a large expansion of the eucalyptus planted area, with approximately 7.6 million hectares. However, there is currently an alarming scenario regarding the productivity of eucalyptus forests in Brazil. In contrast to the growing number of planted areas, forest productivity has been decreasing in the last decade. In 1960, the average productivity of forests was about 10 m3 ha - 1 year. With the advancement of programs for the improvement and implementation of clonal plantations, forest productivity reached its maximum capacity in 2010 with 41.5 m3 ha− 1 year. However, since 2010 the forest productivity curve has been significantly decreasing and has been stagnating between 35 to 36 m³ ha-1 year. In this context, the big question is: Why, even after 51 years of research and development of various technologies, is the productivity curve falling instead of following the expected exponential growth? Many factors may be involved in this phenomenon, such as the choice of genetic material, edaphoclimatic conditions, cultural practices and pest and disease management. Until 1970, Brazilian eucalyptus plantations were considered practically free of diseases and restricted to the states of São Paulo and Minas Gerais. Advances in cultivation techniques as well as in the selection and planting of high productivity genetic materials have allowed the expansion of eucalyptus forests to other regions, the planting of new genetic materials from Eucalyptus spp., Without prior knowledge of their response to levels of susceptibility/resistance to potential pathogens, has stimulated the occurrence of new diseases affecting the productivity of forests. Given this scenario, a comprehensive study of the behavior of diseases as causal agents, distribution and history of occurrence is essential to mitigate losses in eucalyptus plantations due to diseases. Thus, in this study we present an overview of the health of eucalyptus plantations in Brazil. We are based on the ten-year history of pathological diagnosis at the Forest Pathology Laboratory (LPF) of the Federal University of Viçosa (UFV), Viçosa, Minas Gerais, Brazil. In addition, we correlated our findings for the six major pathogens with a bibliometric analysis focused on the number of published articles, authors, countries and institutions.